Case report: Pediatric hepatopulmonary syndrome despite strict weight control after craniopharyngioma surgery - Yoshikawa, Satoko; Takatani, Tomozumi; Takatani, Rieko; Inui, Ayano; Fujisawa, Tomoo; Hamada, Hiromichi (Frontiers in Endocrinology, 2024)
Childhood-onset craniopharyngiomas, though rare, are intracranial malformations that can cause obesity by disrupting the hypothalamus, a condition that often persists even after tumor resection.This severe obesity increases the risk of diabetes and fatty liver disease in childhood. Concurrently, panhypopituitarism, including growth hormone (GH) deficiency, may develop. Notably, some individuals with GH deficiency may exhibit a normal growth rate, making GH therapy unnecessary for growth purposes. However, in these cases, GH therapy may still be beneficial in preventing the progression of nonalcoholic fatty liver disease or nonalcoholic steatohepatitis. Although weight management is traditionally considered the gold standard for preventing liver cirrhosis, its effectiveness can be limited by hypothalamic dysfunction and the difficulty of achieving successful weight control. Our case study highlights a patient with normal growth despite GH deficiency, who did not receive GH replacement therapy and continued to struggle with hypothalamic obesity.Despite effective body weight control, the patient developed hepatopulmonary syndrome, indicating that relying solely on weight management may not be sufficient to prevent liver complications. This case underscores the importance of addressing GH deficiency even when growth is normal. Our findings suggest that GH replacement therapy could be beneficial for preventing liver cirrhosis in such cases.